A pragmatic constructivist approach toward Higher Education management policies – The case of English medium instruction at Aarhus University - Lueg, Klarissa; Lueg, Rainer (Proceedings of Pragmatic Constructivism, 2013)
This paper specifically highlights that discussion on instruction language does not account for stratum specific study strategies. It was presented at the 3rd Actor-reality conference, Aarhus University, October 23-25, 2013.